Beware the woman ebook - Abbott, Megan (2023)
An NPR Best Book of the Year By the "master of thinly veiled secrets often kept by women who rage underneath their delicate exteriors" ( Kirkus Reviews ), Beware the Woman is Megan Abbott at the height of her game. Honey , I just want you to have everything you ever wanted. That’s what Jacy’s mom always told her. And Jacy felt like she finally did. Newly married and with a baby on the way, Jacy and her new husband, Jed, embark on their first road trip together to visit his father, Dr. Ash, in Michigan’s far-flung Upper Peninsula. The moment they arrive at the cottage snug within the lush woods, Jacy feels bathed in love by the warm and hospitable Dr. Ash, if less so by his house manager, the enigmatic Mrs. Brandt. But their Edenic first days take a turn when Jacy has a health scare. Swiftly, vacation activities are scrapped, and all eyes are on Jacy’s condition. Suddenly, whispers about Jed’s long-dead mother and complicated family history seem to eerily impinge upon the present, and Jacy begins to feel trapped in the cottage, her every move surveilled, her body under the looking glass. But are her fears founded or is it simply paranoia, or cabin fever, or—as is suggested to her—a stubborn refusal to take necessary precautions? The dense woods surrounding the cottage are full of dangers, but are the greater ones inside?